How roots and shoots communicate through stressful times. (September 2021) - Li, Hongfei; Testerink, Christa; Zhang, Yanxia
Abstract : When plants face an environmental stress such as water deficit, soil salinity, high temperature, or shade, good communication between above- and belowground organs is necessary to coordinate growth and development. Various signals including hormones, peptides, proteins, hydraulic signals, and metabolites are transported mostly through the vasculature to distant tissues. How shoots and roots synchronize their response to stress using mobile signals is an emerging field of research. We summarize recent advances on mobile signals regulating shoot stomatal movement and root development in response to highly localized environmental cues. In addition, we highlight how the vascular system is not only a conduit but is also flexible in its development in response to abiotic stress. Highlights: Limitations in water uptake in roots and sucrose supply from shoots under abiotic stress can be encoded into signals that regulate the growth and development of distant tissues. Root-localized stress signals trigger changes in xylem hydraulics, mobile peptides, reactive oxygen species (ROS), and Ca 2+, which lead to remote effects and induce shoot stomatal closure. The mobility of HY5 protein and its downstream targets via the phloem conveys shoot-sensed light and temperature information to affect both primary and lateral root growth. Shoot-derived sucrose loading/unloading in the phloem is highly responsive to environmental changes, and triggers signaling pathways that regulate root development. Developmental plasticity of the vasculature in response to abiotic stresses is of key importance for long-distance transport of substances to assist plant stress resilience.